2020
DOI: 10.3390/molecules25051093
|View full text |Cite
|
Sign up to set email alerts
|

Peptides from Natural or Rationally Designed Sources Can Be Used in Overweight, Obesity, and Type 2 Diabetes Therapies

Abstract: Overweight and obesity are among the most prominent health problems in the modern world, mostly because they are either associated with or increase the risk of other diseases such as type 2 diabetes, hypertension, and/or cancer. Most professional organizations define overweight and obesity according to individual body–mass index (BMI, weight in kilograms divided by height squared in meters). Overweight is defined as individuals with BMI from 25 to 29, and obesity as individuals with BMI ≥30. Obesity is the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 306 publications
(403 reference statements)
0
2
0
Order By: Relevance
“…Taken together, it was possible to identify the presence of fragments similar to peptides with described antimicrobial activity, and here only this aspect was explored. However, other intracellular peptide fragments identified in this study may be related to other distinct biological functions, as it has been shown in recent years [ 52 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 56%
“…Taken together, it was possible to identify the presence of fragments similar to peptides with described antimicrobial activity, and here only this aspect was explored. However, other intracellular peptide fragments identified in this study may be related to other distinct biological functions, as it has been shown in recent years [ 52 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 56%
“…Currently, there is an increased consumption of ultra-processed foods, generally rich in hydrogenated fats, simple carbohydrates and low levels of complex carbohydrates [41], as well as a decline in energy expenditure, which is associated with a lack of regular physical activity [42]. An excess of energy ingested and not expended accumulates as body fat, especially in white adipose (WAT) and hepatic tissues, representing one of the main reasons people are overweight and obese [39,43]. The WAT is known for its storing energy function in subcutaneous and visceral depots.…”
Section: Introductionmentioning
confidence: 99%